A case study on the financial performance at Ukhwah Derive by lending money / Nurul Shafira Rahim - Rahim, Nurul Shafira (2009)
This study provides on the financial performance at UKHWAH derive by lending money. The purpose of this study is focus on the financial performance of Koperasi Pendidikan Islam Malaysia Berhad (UKHWAH) deriving by lending money, in order to develop a corporate image of UKHWAH. Financial ratios will play an important role to measure the financial strength of the company. The issue of this study is focus on the financial performance of Koperasi Pendidikan Islam Malaysia Berhad (UKHWAH) deriving by lending money. To analyze that, some method will be introduced through this study in term of data collection and the findings process. In data collection process, all the data will be collected through UKHWAH. The main data to be collected is their financial statements including balance sheet and income statement. From the findings will deal a lot with the ratio analysis, this is supported by Altman (1986) where he found out that ratios measuring liquidity, profitability, operating performance, assets utilization and capital structure and solvency ratio prevailed as the most significant indicators. As a conclusion, UKHWAH is good company based on their financial performance by lending money to members.